y11+11y(y+6)
y11+11y(y+3)
y+3011+11y(y+3)
y+311+11y(y−6)
Correct answer is A
g(y)=y−311+11y2−9
∴
g(y + 3) = \frac{y}{11} + \frac{11}{y^{2} + 6y + 9 - 9}
g(y + 3) = \frac{y}{11} + \frac{11}{y^{2} + 6y}
= \frac{y}{11} + \frac{11}{y(y + 6)}
In the figure, 0 is the centre of the circle ABC, < CED = 30o, < EDA = 40o. What is the size o...
Simplify \frac{1}{5x + 5} + \frac{1}{7x+ 7}...
In the diagram, PQ is a straight line. If m = \frac{1}{2} (x + y + z), find value of m. ...
Simplify log101.5 + 3 log102 − log100.3...
Evaluate \int_1 ^2(6x^2-2x)dx ...
If the angle of a sector of a circle with radius 10.5 cm is 120°, find the perimeter of the sect...
The pie chart above shows the monthly distribution of a man's salary on food items. If he spent ...